Poly(ethylene oxide)‐block‐Polyphosphoester‐graft‐Paclitaxel Conjugates with Acid‐Labile Linkages as a pH‐Sensitive and Functional Nanoscopic Platform for Paclitaxel Delivery. Issue 3 (30th August 2013) - Zou, Jiong; Zhang, Fuwu; Zhang, Shiyi; Pollack, Stephanie F.; Elsabahy, Mahmoud; Fan, Jingwei; Wooley, Karen L.
<x xml:space="preserve">Abstract</x> There has been an increasing interest to develop new types of stimuli‐responsive drug delivery vehicles with high drug loading and controlled release properties for chemotherapeutics. An acid‐labile poly(ethylene oxide)‐block‐polyphosphoester‐graft‐PTX drug conjugate (PEO‐b‐PPE‐g‐PTX G2) degradable, polymeric paclitaxel (PTX) conjugate containing ultra‐high levels of PTX loading is improved significantly, in this second‐generation development, which involves connection of each PTX molecule to the polymer backbone via a pH‐sensitive β‐thiopropionate linkage. The PEO‐b‐PPE‐g‐PTX G2 forms well‐defined nanoparticles in an aqueous solution, by direct dissolution into water, with a number‐averaged hydrodynamic diameter of 114 ± 31 nm, and exhibits a PTX loading capacity as high as 53 wt%, with a maximum PTX concentration of 0.68 mg mL−1 in water (vs 1.7 μg mL−1 for free PTX). The PEO‐b‐PPE‐g‐PTX G2 shows accelerated drug release under acidic conditions (≈50 wt% PTX released in 8 d) compared with neutral conditions (≈20 wt% PTX released in 8 d). Compared to previously reported polyphosphoester‐based PTX drug conjugates, PEO‐b‐PPE‐g‐PTX G1 without the β‐thiopropionate linker, the PEO‐b‐PPE‐g‐PTX G2 shows pH‐triggered drug release property and 5‐ to 8‐fold enhanced in vitro cytotoxicity against two cancer cell lines.